Assessment of the viability and treatment response of bone metastases in patients with metastatic castration-resistant prostate cancer using choline PET/CT. Issue 23 (11th June 2021) - Kitajima, Kazuhiro; Yamamoto, Shingo; Kawanaka, Yusuke; Komoto, Hisashi; Shimatani, Kimihiro; Hanasaki, Takeshi; Taguchi, Motohiro; Nagasawa, Seiji; Yamada, Yusuke; Kanematsu, Akihiro; Yamakado, Koichiro
Abstract : Abstract: This study aimed to evaluate the clinical use of choline-PET/CT for discriminating viable progressive osteoblastic bone metastasis from benign osteoblastic change induced by the treatment effect and evaluating the response of bone metastasis to treatment in metastatic castration-resistant prostate cancer (mCRPC) patients. Thirty patients with mCRPC underwent a total of 56 11 C-choline-PET/CT scans for restaging, because 4 patients received 1 scan and 26 had 2 scans. Using 2 (pre- and post-treatment) 11 C-choline-PET/CT examinations per patient, treatment response was assessed according to European Organization for Research and Treatment of Cancer (EORTC) criteria in 20 situations, in which only bony metastases were observed on 11 C-choline-PET/CT scans. Viable bone metastases and osteoblastic change induced by the treatment effect were identified in 53 (94.6%) and 29 (51.8%) of 56 11 C-choline-PET/CT scans, respectively. In 27 cases (48.2%), 11 C-choline-PET/CT scans could discriminate the 2 entities. The mean SUVmax of the metastatic bony lesions was 5.82 ± 3.21, 5.95 ± 3.96, 6.73 ± 5.04, and 7.91 ± 3.25 for the osteoblastic, osteolytic, mixed, and invisible types, respectively. Of the 20 situations analyzed, CMR, PMR, SMD, and PMD, as determined by the EORTC, were seen in 1, 2, 3, and 14 cases, respectively. Of the 13 patients with increasing PSA trend, all 13 showed PMD. Of the 2 patients with PSA response of <50%, both 2 showed SMD. Of the 5 patients with PSA response of ≥50%, 1 showed CMR, 2 showed PMR, 1 showed SMD, and 1 showed PMD. Choline-PET/CT is very useful to discriminate viable progressive osteoblastic bone metastasis from osteoblastic change, and assess treatment response of bone metastases in mCRPC.